2016
DOI: 10.1111/nmo.12869
|View full text |Cite
|
Sign up to set email alerts
|

The rising cost of hospital care for children with gastroparesis: 2004–2013

Abstract: The financial burden of hospitalization for pediatric GP has increased dramatically from 2004 to 2013, driven by a rise in number of hospitalizations and unique patients hospitalized each year. Cost and LOS per hospitalization remain stable. Unlike in adults, hospitalizations for DYS/UFD have also increased, suggesting that the increase in hospitalizations for GP is not secondary to changing diagnostic practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 10 publications
0
37
0
1
Order By: Relevance
“…It remains unclear whether this is true for children and whether it is simply due to improved awareness and more clinically diagnosed cases . A nationwide inpatient database study of over 4000 children with gastroparesis (median age 8 years, IQR 2‐14) noted a dramatic increase in the financial burden of hospitalization for pediatric gastroparesis during years 2004‐2013 . This study found that, unlike in adults, hospitalizations for functional gastrointestinal (GI) disorders have simultaneously increased, suggesting that the rise in gastroparesis admissions may not be simply secondary to changing awareness and diagnostic practices.…”
Section: Resultsmentioning
confidence: 97%
“…It remains unclear whether this is true for children and whether it is simply due to improved awareness and more clinically diagnosed cases . A nationwide inpatient database study of over 4000 children with gastroparesis (median age 8 years, IQR 2‐14) noted a dramatic increase in the financial burden of hospitalization for pediatric gastroparesis during years 2004‐2013 . This study found that, unlike in adults, hospitalizations for functional gastrointestinal (GI) disorders have simultaneously increased, suggesting that the rise in gastroparesis admissions may not be simply secondary to changing awareness and diagnostic practices.…”
Section: Resultsmentioning
confidence: 97%
“…While the prevalence among children is unknown, the past decade has seen a dramatic increase in gastroparesis-associated hospitalizations. [25] In children 70% of gastroparesis is idiopathic or post-viral, with the remaining 30% due to medications or post-surgery. Various pathophysiologic causes have been proposed, including abnormalities of extrinsic gastric innervation, loss of interstitial cells of Cajal (ICCs), hypoganglionosis, and inflammatory degeneration of myenteric neurons.…”
Section: Gastroparesismentioning
confidence: 99%
“…It occurs in up to 4% of adults, but no prevalence data are available in children . A nationwide database survey did document a dramatic increase in hospitalizations for pediatric gastroparesis during years 2004–2013 . Confirming the diagnosis of gastroparesis can be challenging, as testing protocols vary and there are no standardized, age‐based pediatric normative data for comparison .…”
Section: Overview Of Common Pediatric Gi Motility Disordersmentioning
confidence: 99%
“…7 A nationwide database survey did document a dramatic increase in hospitalizations for pediatric gastroparesis during years 2004-2013. 9 Confirming the diagnosis of gastroparesis can be challenging, as testing protocols vary and there are no standardized, age-based pediatric normative data for comparison. 10 As pharmacological treatment options are very limited, nutrition interventions are often essential components of therapy.…”
Section: Gastroparesismentioning
confidence: 99%